2012
DOI: 10.4062/biomolther.2012.20.5.457
|View full text |Cite
|
Sign up to set email alerts
|

Kalopanaxsaponin B Ameliorates TNBS-Induced Colitis in Mice

Abstract: The stem-bark of Kalopanax pictus (KP, family Araliaceae), of which main constituent is kalopanaxsaponin B, has been used for asthma, rhinitis, and arthritis in Chinese traditional medicine. To clarify anticolitic effect of KP, we examined anti-inflammatory effect of KP extract and kalopanaxsaponin B in lipopolysaccharide (LPS)-stimulated peritoneal macrophage and 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitic mice. Of KP extracts, KP BuOH-soluble fraction most potently inhibited LPS-induced IL-1β,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Macrophages within tissues play an essential role in the initiation, development, and resolution of inflammation [ 8 11 ]. Macrophages are white blood cells that are differentiated from monocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages within tissues play an essential role in the initiation, development, and resolution of inflammation [ 8 11 ]. Macrophages are white blood cells that are differentiated from monocytes.…”
Section: Introductionmentioning
confidence: 99%
“…CLM ( ceriporia lacerata mycelia) plays an immunostimulatory role in macrophages via TLR4-induced TNF-α, IL-1β, and IL-6 production ( 35 ). In previous reports, KP treatment inhibited LPS- or TNBS-induced TNF-α and IL-6 expression and production in vitro and in vivo ( 40 , 42 , 43 ). In vitro and in vivo studies revealed that NN reduced inflammation through downregulated proinflammatory cytokines TNF-α, IL-6, IL-1β, and IFN-γ in LPS- and DSS-induced inflammation model ( 44 – 46 ).…”
Section: Discussionmentioning
confidence: 68%
“…A previous study reported that Red Platycodon grandiflorus root extract could enhance immunity by increasing the NF-κB phosphorylation level as well as the p38 MAPK-induced NF-κB activation in RAW 264.7 cells ( 39 ). KP or herbal mixture including KP showed anti-inflammatory effects by down-regulating IκBα, NF-κB, and JNK/p38 MAP kinase signaling pathways ( 13 , 14 , 40 43 ). In addition, NN exerts anti-inflammatory effects on LPS-stimulated RAW 264.7 macrophages through inhibition of NF-κB and MAPK pathways ( 44 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…[49] Several mechanisms have been proposed to explain the antiinflammatory action of phytoconstituents: (i) Antioxidative and free radical scavenging activities, (ii) modulation of cellular activities of inflammation related to cells, (iii) modulation of pro-inflammatory enzyme activities, and (iv) modulation of pro-inflammatory gene expression. [49][50][51][52][53][54][55][56] Phytochemical screening of the RCRE revealed the presence of carbohydrate, glycosides, saponins, flavonoids, alkaloids, tannins, and phenolic compounds. These phytoconstituents have been found to be effective in various models of IBD and may explain the antioxidant and anti-inflammatory activity of RCRE.…”
Section: Discussionmentioning
confidence: 99%